2005
DOI: 10.4103/0019-5359.16255
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence in pregnancy in North Indian women

Abstract: BACKGROUND: Domestic violence against pregnant women in the Indian context, violence against women is frequently by family members other than the spouse/ intimate partner/husband. AIMS: To study the incidence of domestic violence in pregnant North Indian women and the demographic features which put women at high risk for domestic violence. STUDY DESIGN: A prospective study at the Government Medical College and Hospital, Chandigarh from January 2004 to December 2004. PARTICIPANTS: Nine hundred and ninety-one pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 8 publications
4
67
3
2
Order By: Relevance
“…In the exceptional case, the perpetrator was the woman's father-in-law. Khosla et al (19) reported that 51.8% of women in their study experienced violence perpetrated by their husbands' families. The current study was limited, because it employed a small number of subjects.…”
Section: Discussionmentioning
confidence: 87%
“…In the exceptional case, the perpetrator was the woman's father-in-law. Khosla et al (19) reported that 51.8% of women in their study experienced violence perpetrated by their husbands' families. The current study was limited, because it employed a small number of subjects.…”
Section: Discussionmentioning
confidence: 87%
“…Most common form of physical violence faced by women was Grade I(56.86%), followed by grade II(31.37%) & then Grade III(11.76%), and the perpetrators of violence were the women's husband (85.71%) and mother in law (29.52%) , similar to study done by Khosla. A. H [2]. The perceived risk factor were Poverty (21.9%) & Addiction in husbands(20%), as seen in study done by S. Mitra [3].…”
Section: Discussionmentioning
confidence: 93%
“…chocking, strangling, use of knife or stick for beating in 11.76%(6) of respondents [2]. The perpetrators of violence were mostly husbands' in 85.71%(90) of cases and mother's in law 29.52%(31).…”
Section: IIImentioning
confidence: 99%
“…In India, the figures of IPV during pregnancy have ranged from 13% to 28%, depending on the sample studied and nature of the perpetrator (Peedicayil et al, 2004;Khosla et al, 2005). For example, 22% of women attending an antenatal clinic in central India reported physical violence (Purwar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%